Macroeconomic policy regimes in emerging markets: the case of Latvia - Milka Kazandziska (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
This paper's goal is to analyse economic development in Latvia using the concept of a macroeconomic policy regime (MPR). An MPR consists of foreign economic policy, industrial policy, the financial system, wage policy, monetary policy and fiscal policy. This paper, furthermore, aims to explore the functionality of the development of these elements in Latvia based on one normative model of an MPR using a post-Keynesian approach. This paper suggests that to achieve a growth consistent with an external balance, foreign economic policy and industrial policy should be given high priority in restructuring the economy towards production and exports of high value-added products. The financial system needs to provide sufficient finance for the business sector and maintain the stability of the financial sector, while monetary policy will be in charge of providing low-cost finance to the financial system, secure its stability and maintain the stability of the exchange rate. Wage policy would be in charge of stabilising the inflation rate. Fiscal policy's main tasks would be to reduce the shocks to aggregate demand and reduce income inequality. It will be argued that the institutional changes in Latvia paved the way for a dysfunctional policy mix, of the sort that led to unstable economic development, high current account deficits, capital flow volatility, financial system instability, inflation rate volatility, and increasing income inequality.
Keywords: E02; E58; E61; E65; F41; F43; 330; macroeconomic regime; open economy policies; emerging countries; industrial policy; Latvia